(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The communication between family members has a significant impact on their mental health. The family relationships help children develop healthy personalities. Children who grow up in relationships based on mutual respect, love, tolerance and self-sacrifice develop healthy personalities. Children suffer the most from communication disorders. When a child sees his parents discussing their problems and solving them in a positive way, he finds an opportunity to prepare for the problems he may face in his future life. The goal of this research - to study the influence of the family environment on the formation of a child’s personality, to obtain scientific and theoretical knowledge on the elimination of family conflicts that affect the development of children, refraining from arguments in the presence of children and creating favorable conditions for communication. Research methodology - approaches and ideas put forward in classical and modern psychology, applicable to family relationships and their influence on the formation of a child’s personality, theories based on the study of problems related to the development of a child’s personal qualities. The study analyzed family upbringing, influencing the formation of the personality of children, the attitude of parents to children and the parents among themselves, and positive and negative results were also identified.